Genocide: a world history - Naimark, Norman M. (The new Oxford world history, 2017)
Introduction -- The ancient world -- Warrior genocides -- The Spanish conquest -- Settler genocide -- Modern genocides -- Communist genocides -- Anti-communist genocide -- Genocide in the post-Cold War world -- Conclusion